Liver Function is Associated With Response to Clopidogrel Therapy in Patients Undergoing Angioplasty and Stenting. (October 2016) - Gremmel, Thomas; Mueller, Markus; Koppensteiner, Renate; Panzer, Simon
The relationship between liver function and clopidogrel response has not been studied so far. We therefore sought to investigate the associations between 3 parameters of liver synthesis and on-treatment platelet reactivity to adenosine diphosphate in patients on dual antiplatelet therapy. On-treatment platelet reactivity was determined by the VerifyNow P2Y12 assay in 316 patients undergoing angioplasty with stent implantation for cardiovascular disease. Cholinesterase, serum albumin, and total cholesterol levels were measured by internationally standardized assays in the hospital's central laboratory. On-treatment platelet reactivity by the VerifyNow P2Y12 assay correlated inversely with cholinesterase, serum albumin, and total cholesterol levels (all P ≤ .02). The inverse associations of cholinesterase and serum albumin levels with platelet reactivity remained significant after adjustment for cytochrome P450 loss-of-function polymorphisms and other factors that were previously associated with high on-treatment residual platelet reactivity (HRPR; both P < .05). Patients without HRPR by the VerifyNow P2Y12 assay had significantly higher levels of serum albumin and total cholesterol than patients with HRPR (both P = .008). In conclusion, liver function is associated with response to clopidogrel therapy in patients undergoing angioplasty and stenting for cardiovascular disease.